Teaching Methods and Tools Used In Food Safety Extension Education Programs in the North Central Region of the United States - Robert A. Martin; Vikram Swaroop Chandra Koundinya (International Journal of Agricultural Management and Development, 2011)
One of the ways to ensure food safety is to educate thepublic. Of the organizations providing food safety educationin the United States (U.S.), the Cooperative Extension System(CES) is one of the most reliable. The effectiveness CESprograms depends not only on what is being taught but also onhow it is taught. Both a needs-based curriculum and how thatcurriculum is delivered are equally important. This descriptivecross-sectional study using a disproportional stratified randomsample identified the teaching methods and tools being used byfood safety extension educators of the CES of North CentralRegion (NCR). A Likert-type scale administered to extensioneducators revealed that they were adopting a balanced use ofteaching methods and tools, and using learner-centered teachingmethods in their programs. However, distance education, casestudies and podcasts, which are commonly used in educationprograms, were not being used extensively. We recommend thatfood safety extension educators of NCR should increase the useof these two teaching methods and tool while continuing to usethe current ones. This study has implications for improving foodsafety education delivery to clients in the NCR and for designinginservice education for food safety extension educators